2021
DOI: 10.3390/life11090982
|View full text |Cite
|
Sign up to set email alerts
|

Narrow Precursor Mass Range for DIA–MS Enhances Protein Identification and Quantification in Arabidopsis

Abstract: Data independent acquisition–mass spectrometry (DIA–MS) is becoming widely utilised for robust and accurate quantification of samples in quantitative proteomics. Here, we describe the systematic evaluation of the effects of DIA precursor mass range on total protein identification and quantification. We show that a narrow mass range of precursors (~250 m/z) for DIA–MS enables a higher number of protein identifications. Subsequent application of DIA with narrow precursor range (from 400 to 650 m/z) on an Arabido… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In essence, scientists must balance three key factors: (I) cycle time, (II) covered mass range, and (III) the size of the isolation window. Historically, gas phase fractionations were employed to alleviate slow acquisition speed, meaning that the same sample was injected repeatedly, each time focusing on a different narrow mass range. ,, Recently, it was shown that focusing on narrow mass ranges can benefit protein coverage. , The rationale can be compared to using a magnifying glass on a painting: while the overall picture is not represented, it is possible to observe intricate details that might be overlooked at a broader glance. As we do not need to detect and quantify every peptide of a protein for its quantitation, it is sufficient to capture a smaller mass range to quantify less precursors overall, which in turn represent more proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, scientists must balance three key factors: (I) cycle time, (II) covered mass range, and (III) the size of the isolation window. Historically, gas phase fractionations were employed to alleviate slow acquisition speed, meaning that the same sample was injected repeatedly, each time focusing on a different narrow mass range. ,, Recently, it was shown that focusing on narrow mass ranges can benefit protein coverage. , The rationale can be compared to using a magnifying glass on a painting: while the overall picture is not represented, it is possible to observe intricate details that might be overlooked at a broader glance. As we do not need to detect and quantify every peptide of a protein for its quantitation, it is sufficient to capture a smaller mass range to quantify less precursors overall, which in turn represent more proteins.…”
Section: Resultsmentioning
confidence: 99%
“…6,29,30 Recently, it was shown that focusing on narrow mass ranges can benefit protein coverage. 31,32 The rationale can be compared to using a magnifying glass on a painting: while the overall picture is not represented, it is possible to observe intricate details that might be overlooked at a broader glance.…”
Section: Setup Of Narrow Mass Range Dia Methodsmentioning
confidence: 99%
“…Last, we refined the method of HRMS data acquisition, which fundamentally controls the success of peptide sequencing and hence the fidelity of protein identifications. During DDA, historically the most commonly employed approach in bottom-up proteomics, the most abundant precursor ions are preferred for fragmentation, albeit at the expense of quantitative bias toward reporting on molecules at high concentration. , As an alternative, DIA schedules fragmentation for precursor ions over a wide m / z window, thus enhancing the likelihood of sequencing low-abundance peptides for trace-level protein identification. The DIA data acquisition parameters were kept consistent with the DDA method when possible to facilitate a direct comparison of the results between the two methods. We selected 12 m / z windows for the DIA method based on recent publications using Orbitrap hybrid and tribrid instruments. , Surprisingly, DIA of the same midbrain proteome returned 4470 proteins (Table S4), slightly lower than the 4684 proteins (Table S2) that were detected by the DDA method on the same sample (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…A targeted quantification strategy is recommended for further analysis of proteins of interest because this provides more accurate quantification and is less likely to have missing values, particularly in the 15 N labeled samples ( Bi et al, 2021 ; Reyes et al, 2021 ). In addition to targeted analysis, data-independent acquisition (DIA) ( Zhang and Bensaddek, 2021 ) can also be utilized, which can be done in label free samples or combined with 15 N metabolic labeling in the future. DIA benefits from having few missing values, but more efforts will be needed to deconvolve the mixed MS 2 spectra in DIA datasets.…”
Section: Resultsmentioning
confidence: 99%